Residential greenness and mortality in oldest-old women and men in China: a prospective cohort study. (October 2018) - Ji, John S; Zhu, Anna; Bai, Chen; James, Peter; Yan, Lijing; Zeng, Yi; Wu, Chih-Da
Abstract: Background: Exposure to nature, or greenness, may affect health through several pathways, including health-promoting activities and influencing psychological wellbeing. How greenness affects vulnerabilities due to old-age health has not been assessed. We assessed the relationship between residential greenness and mortality in an elderly cohort representative of China. Methods: We used the prospective China Longitudinal Healthy Longevity Survey (CLHLS), a cohort representative of general elderly population in China. Our exposure was assessed by satellite-derived Normalised Difference Vegetation Index (NDVI) in 250 m and 1250 m radius around each participant's residential addresses between 2000 to 2014. We calculated cumulative NDVI, contemporaneous NDVI, and changes in NDVI values over time. We used all-cause mortality, excluding accidental death, as our outcome. The CLHLS was granted ethical approval from Research Ethics Committees of Peking University and Duke University. All subjects signed written informed consent before interview. Findings: We followed up 3839 people at least 80 years of age between 2000 and 2014 totalling 13 253 person-years. The mean age at baseline was 92 years (SD 7·6). During 14 years of follow up, we recorded 3244 deaths. We used cox-proportional hazard models, adjusted for age, gender, ethnicity, urban/rural residence, geographical region, education years, occupation before age 60 years, marital status, smoking status, alcohol consumption, exercise, financial support, co-residence status, and annual average PM2·5 . Compared with the lowest quartile of contemporaneous NDVI values, the highest quartile had a decreased risk of mortality (hazard ratio [HR] 0·78, 95% CI 0·70–0·87, for the 250 m radius; HR 0·77, 0·69–0·85, for the 1250 m radius). No significant effects on mortality were found for cumulative NDVI measurement (HR 1·12, 95% CI 0·99–1·27, for the 250 m radius; HR 1·09, 0·96–1·23, for the 1250 m radius). Compared with people living in regions with a significant decrease in NDVI from 2000 to 2014 (p <0·05), among people living in region with a significant increase, we saw a HR of 0·90 (95% CI 0·80–1·01) for the 250 m radius, and 0·88 (0·79–0·99) for the 1250 m radius. Interpretation: Our research suggests that more green space might promote healthy longevity, which has policy implications for eco-civilisation and preparing for ageing societies in China. Funding: None.